2020
DOI: 10.1002/ajh.26064
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of multiple myeloma patients refractory to venetoclax: A single center experience

Abstract: Stacy Diao provided study design, collected and analyzed data, and prepared the manuscript. E Dan Nichols provided study design, analyzed data, and reviewed and edited the manuscript. Courtney DiNardo and Marina Konopleva contributed patients, and reviewed and edited the manuscript.Jing Ning and Wei Qiao conducted statistical analysis, results interpretation, and reviewed and edited the manuscript. Abhishek Maiti reviewed and edited the manuscript. Adam J. DiPippo provided study design, collected and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The first retrospective study to assess real-world outcomes from the time of venetoclax refractoriness demonstrated a median OS of 31.4 months. These findings support the use of venetoclax early in the treatment of the t(11;14) patient group, challenging the notion that venetoclax resistance results in a more aggressive disease phenotype ( 81 ).…”
Section: Translocation T(11;14) and Precision Intervention In MMmentioning
confidence: 72%
“…The first retrospective study to assess real-world outcomes from the time of venetoclax refractoriness demonstrated a median OS of 31.4 months. These findings support the use of venetoclax early in the treatment of the t(11;14) patient group, challenging the notion that venetoclax resistance results in a more aggressive disease phenotype ( 81 ).…”
Section: Translocation T(11;14) and Precision Intervention In MMmentioning
confidence: 72%
“…Furthermore, in a single-institution retrospective analysis of 68 patients selected for venetoclax treatment based on the presence of t(11;14), the ORR was 71% (48.5% VGPR or better) with a median progression-free survival (PFS) of 14.1 months. 53 For patients with less than 3 prior lines of therapy, the PFS was 23.2 months. These promising results have led to an ongoing Phase III study randomizing patients with t(11;14) myeloma to either venetoclax and dexamethasone or pomalidomide and dexamethasone.…”
Section: Clinical Studies Of Venetoclax In Multiple Myelomamentioning
confidence: 99%
“…However, in a retrospective analysis of 38 patients who progressed on venetoclax, 84% went on to receive an additional line of therapy and experienced a median OS of 31.4 months from the time of venetoclax refractoriness, arguing against any inferior outcomes post-venetoclax. 53 The safety concerns from this trial have increased scrutiny of other venetoclax combination trials in myeloma and led to adjustments such as routine antimicrobial prophylaxis and closer infectious monitoring.…”
Section: Dovepressmentioning
confidence: 99%
“…A retrospective study, using functional profiling of venetoclax sensitivity and presence of t (11;14) as a selection criteria involving 68 patients, reached ORR of 71%. 9 In an ongoing Phase III study, only t(11;14) RRMM patients will be randomized to venetoclax and dexamethasone or pomalidomide and dexamethasone. 10 In this study, we used low dose venetoclax (400 mg daily) in 25 RRMM or relapsing AL-amyloidosis patients harboring t (11;14), ORR was 44% with manageable AE and no associated deaths.…”
Section: Introductionmentioning
confidence: 99%
“…The ORR in the phase II part of trial was 48%. A retrospective study, using functional profiling of venetoclax sensitivity and presence of t(11;14) as a selection criteria involving 68 patients, reached ORR of 71% 9 . In an ongoing Phase III study, only t(11;14) RRMM patients will be randomized to venetoclax and dexamethasone or pomalidomide and dexamethasone 10 .…”
Section: Introductionmentioning
confidence: 99%